ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT DI DESA TUMBU KECAMATAN TOPOYO KABUPATEN MAMUJU TENGAH - Dermawan, Dermawan; Alam, Max Nur; Tangkesalu, Dance (AGROTEKBIS, 2019)
This study aims to calculate the income received by oil palm farmers in Tumbu Village, Topoyo subdistrict, Central Mamuju regency. This research has been carried out in Tumbu Village in February-March 2017. Respondents in this study is farmers palm oil in the Village Tumbu, Determination of respondents using simple random sampling number of samples as much as 31 farmers oil palm or 14% of 225 farmers oil palm. Analysis used in this research is farming     income analysis. The results of the analysis show that the amount of production 47,964.06 kg/1.64 ha/year or 29,246.37kg/ha/yearwith sale price fresh fruit bunches Rp1,543/kg, total cost                Rp 9,643,985.47/1.64ha/yearorRp5,880,478.93/ha/yearandrevenueRp74,008,551.50/1.64ha/year     or amount Rp 45,127,165.50/ha/year, so farmers? income isRp 64,364,598.30/1.64ha/year              or amountRp 39,246,706.30/ha/year.